ANALISIS QUALITY OF SERVICE PADA JARINGAN INTERNET DINAS LINGKUNGAN HIDUP DAN KEBERSIHAN - Aryandi, Heryn Achmad; Tatuhey, Emy L; Lahallo, Jim (Universitas Multi Data Palembang, 2023)
As an agency with important responsibilities, the Jayapura City Environment and Hygiene Office (DLHK) requires reliable internet access to manage environmental data, communicate with related parties, and monitor environmental conditions. However, network quality issues such as low access speed, frequent interruptions, inadequate security, and incompatibility with devices and applications hinder DLHK's performance efficiency. To overcome these problems, a Quality of Service (QoS) analysis was conducted on the DLHK internet network. The purpose of this analysis is to evaluate the quality of the existing network and identify potential problems that could affect DLHK's performance. The results of this QoS analysis will provide recommendations to improve the quality of the DLHK internet network in Jayapura City. Based on the analysis results, four main parameters were evaluated: delay, Packet Loss, jitter, and throughput. The average delay value is 71.5, Packet Loss 27, jitter 0.08, and throughput 0.2386. These parameters were compared with the network performance standards of the TIPHON version. The results show that delay and jitter fall into the excellent category with an index of 4, while Packet Loss and throughput fall into the poor category with an index of 1.